Geometric Profile of the Tibial Plateau Cartilage Surface Is Associated With the Risk of Non-Contact Anterior Cruciate Ligament Injury - Beynnon, Bruce D. (J Orthop Res, 2013)
The purpose of this study was to determine if geometry of the articular surfaces of the tibial plateau is associated with non-contact anterior cruciate ligament (ACL) injury. This was a longitudinal cohort study with a nested case-control analysis. Seventy-eight subjects who suffered a non-contact ACL tear and a corresponding number of controls matched by age, sex, and sport underwent 3 T MRI of both knees. Surface geometry of the tibial articular cartilage was characterized with polynomial equations and comparisons were made between knees on the same person and between ACL-injured and control subjects. There was no difference in surface geometry between the knees of the control subjects. In contrast, there were significant differences in the surface geometry between the injured and normal knees of the ACL-injured subjects, suggesting that the ACL injury changed the cartilage surface profile. Therefore, comparisons were made between the uninjured knees of the ACL-injured subjects and the corresponding knees of their matched controls and this revealed significant differences in the surface geometry for the medial (p < 0.006) and lateral (p < 0.001) compartments. ACL-injured subjects tended to demonstrate a posterior-inferior directed orientation of the articular surface relative to the long axis of the tibia, while the control subjects were more likely to show a posterior-superior directed orientation.